Civil law profiles of health and care: informed consent and ethical bargaining autonomy (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In the light of disquisitions concerning the doctrinal and jurisprudential formant, the present work proposes to analyse the civil law qualification of informed consent from a philosophical point of view with the aid of an ordering criterion such as the logos of legal science: axiology, which is not merely the logical interpretation of a balancing of principles but rather the systematic interpretation of the legal system regardless of the sharing of the modus cogitandi since science deploys its efficacy through the search for a synthesis between thesis and antithesis.
Keywords: Civil law; health and care; artificial intelligence; international law; bargaining autonomy